A study on the implementation of group work learning in secondary ESL classroom / Nur Bazilah Khairudin - Khairudin, Nur Bazilah (Faculty of Education, 2014)
The study aims to investigate on the implementation of group work learning in secondary ESL classroom. This study has several purposes where it wants to identify the positive and negative effects towards having group work learning in secondary ESL classroom, students' general perspectives over learning in group, the reasons for positive and negative impacts of group work learning and finally, the problems with group work learning. This research was done by quantitative research method where questionnaires were used to gather data from the respondents. The samples of the study consist of 60 students from Form 2 and Form 4 students of Sekolah Menengah Kebangsaan Seri Garing, Rawang. The findings show that respondents believe that by group work learning they become friends with group members, however, they only prefer to be grouped with their friends and prefer to choose the group members. Furthermore, according to students' perspectives over learning in group, students find that group work learning is fun. Besides, in fourth and fifth research questions, students were asked on the reasons for positive and negative impacts of group work learning, it can be seen that most respondents believe that group work learning can improve several students' skills such as problem-solving, interpersonal and language skills. Meanwhile, the reasons for negative impacts are deviating attention and selfdoubt as stated by most respondents. Finally, most respondents believe that uninvolved or uncooperative group members are the critical problem of group work learning in secondary ESL classroom. On the basis of the results of this research, it can be concluded that group work learning in secondary ESL classroom has it pros and cons to be weighed before implementing it in the secondary ESL classroom.